2011
DOI: 10.1164/rccm.201103-0412oc
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Murine Model of Severe Pulmonary Arterial Hypertension

Abstract: These data describe a novel murine model of PAH, which displays many of the hallmarks of the human disease, thus opening new avenues of investigation to better understand PAH pathophysiology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
246
6

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 228 publications
(274 citation statements)
references
References 45 publications
16
246
6
Order By: Relevance
“…While we found a small number of occlusive arteriolar lesions in SuHx mice and none in normoxic or VehHx mice 10 weeks after the end of hypoxia, these were very rare and thus unlikely to have contributed greatly to PH in these animals. In contrast to Ciuclan et al, 6 we did not observe any angiobliterative lesions in SuHx mice after 3 weeks of hypoxia. Hence, according to our results, SuHx produces sustained PH and moderate RV dysfunction as judged by TAPSE but no significant angioobliterative pulmonary vascular disease in mice.…”
Section: Discussioncontrasting
confidence: 99%
“…While we found a small number of occlusive arteriolar lesions in SuHx mice and none in normoxic or VehHx mice 10 weeks after the end of hypoxia, these were very rare and thus unlikely to have contributed greatly to PH in these animals. In contrast to Ciuclan et al, 6 we did not observe any angiobliterative lesions in SuHx mice after 3 weeks of hypoxia. Hence, according to our results, SuHx produces sustained PH and moderate RV dysfunction as judged by TAPSE but no significant angioobliterative pulmonary vascular disease in mice.…”
Section: Discussioncontrasting
confidence: 99%
“…While this is higher than values normally reported at sea level (around 20%; Ciuclan et al, 2011), it is much lower than the values reported in rats in our present and past (Lumbroso et al, 2012) studies. Protection against elevated pulmonary hypertension is common in species adapted to high altitude, which demonstrate thinner pulmonary vessel walls with a reduced number of muscular cells (Tucker and Rhodes, 2001).…”
Section: Discussioncontrasting
confidence: 84%
“…For example, in the Sugen5416/hypoxia mouse model of PAH, the increase in RVSP values from 32 to 50 mmHg was induced when >60% of pulmonary arterioles were affected by muscularization (27% partial muscularization and 37% full muscularization). 32 In fact, our data are similar to other murine models showing that pulmonary arterial remodeling, even when present at an advanced degree, does not necessarily cause pulmonary hypertension. 33 These observations support the clinical studies showing that pulmonary vascular remodeling has limited diagnostic value because they are present in all forms of severity of pulmonary hypertension 27 ; it may explain, at least to some extent, the discrepancy between significant vascular remodeling associated with only mild elevation of pulmonary arterial pressure, often observed in PAH patients.…”
Section: Treatment Of K0supporting
confidence: 89%